Enhanced crystallization kinetics of bacterially synthesized poly(3-hydroxybutyrate-co-3-hydroxyhexanate) with structural optimization of oxalamide compounds as nucleators. (August 2018) - Xu, Pengwu; Cao, Ying; Lv, Pei; Ma, Piming; Dong, Weifu; Bai, Huiyu; Wang, Wei; Du, Mingliang; Chen, Mingqing
Abstract: Bacterially synthesized poly (3-hydroxybutyrate- co -3-hydroxyhexanate) (PHBH) has attracted much attention as biodegradable plastics and potential biomaterials. However, the crystallization rate of PHBH is very low, which limits its application in plastic field. Herein, oxalamide compounds (OXAn ) with a formula of C6 H5 NHCOCONH(CH2 )n NHCOCONHC6 H5 (n = 2, 4, 8, 12) were tailor-made as nucleators to improve the crystallization behaviors of PHBH. The effect of aliphatic spacer length of OXAn, i.e., -(CH2 )n -on the nucleation behavior was investigated. The OXAn would assemble into shish-like superstructures and PHBH crystals preferred to grow on the surfaces of the shish. The crystallization rate of PHBH/OXAn blends increased with the spacer length of OXAn up to n = 8 and then leveled off, which trend was consistent with the nucleation activity (Ψ) and the nucleation constant (Kg ) of the OXAn . Meanwhile, the OXAn increased the nuclei density of the PHBH while inhibited its secondary crystallization, resulting in a superior and steady mechanical performance of PHBH materials. This work provides a scientific approach to design the optimal structure of OXAn as nucleators for PHBH materials, which may broaden the application range of PHBH materials. Highlights: Crystallization kinetics of PHBH was greatly enhanced. The t1/2 of PHBH was decreased by 93% after adding OXAn . PHBH/OXAn with superior and steady mechanical performance was achieved. A scientific approach to optimal structure of nucleators was provided.